Manajemen Mutu dan Supervisi Pendidikan - Idrus, Sulkifli; Reskiah; Muqim, Faiz; Maulana, Muh. Muhajir; Juliati, Tiwi; Surahman, Muhammad Syahrullah; Sari, Arwidya Putri Indah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Educational quality management and educational supervision management are two key elements in improving the quality of educational institutions. This study aims to analyze the strategic role of both aspects in supporting the achievement of effective and efficient educational goals. Educational quality management is oriented towards systematic efforts to ensure that all components of education operate in accordance with established quality standards, through a process of planning, implementation, supervision, and continuous evaluation. On the other hand, educational supervision management is focused on professional development of educators, especially teachers, in order to improve competence, performance, and quality of learning. The results of this study indicate that the integration of educational quality management and supervision can create a strong quality culture in schools, improve the learning process, and improve student learning outcomes. Therefore, both need to be developed consistently as the main strategy in managing quality education.